2012
DOI: 10.5402/2012/391631
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in the Management of Gastroesophageal Reflux Disease: A Review

Abstract: Gastroesophageal reflux disease (GERD) is a chronic disorder of the upper gastrointestinal tract with global distribution. The incidence is on the increase in different parts of the world. In the last 30 to 40 years, research findings have given rise to a more robust understanding of its pathophysiology, clinical presentation, and management. The current definition of GERD (The Montreal definition, 2006) is not only symptom-based and patient-driven, but also encompasses esophageal and extraesophageal manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 108 publications
0
24
0
2
Order By: Relevance
“…Among European and American populations, the approximate prevalence rate of GERD has been reported to be between 10%-20%, while in Asia, this number is below 10% [3,4]. Possible risk factors associated with the condition include age, obesity, alcohol consumption, cigarette smoking and presence of hiatus hernia [5]. Mahadeva et al concluded that GERD is more common among persons of British origin compared to people of the South-East Asian dyspeptic population, suggesting that race and/or western lifestyle are crucial contributors to the occurrence of GERD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among European and American populations, the approximate prevalence rate of GERD has been reported to be between 10%-20%, while in Asia, this number is below 10% [3,4]. Possible risk factors associated with the condition include age, obesity, alcohol consumption, cigarette smoking and presence of hiatus hernia [5]. Mahadeva et al concluded that GERD is more common among persons of British origin compared to people of the South-East Asian dyspeptic population, suggesting that race and/or western lifestyle are crucial contributors to the occurrence of GERD [6].…”
Section: Introductionmentioning
confidence: 99%
“…The principles of treatment include lifestyle modifications and control of gastric acid secretion using drugs or surgical treatment with corrective anti-reflux surgery, if required. 24 Multi-drug therapy may be important in bronchial asthma and COPD patients with GERD. The efficacy of proton pump inhibitors may differ between regurgitation-related symptoms and dysmotility related symptoms in asthma patients and COPD patients with GERD.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of certain drugs that can relax the LES will also predispose to GER. These drugs include the anticholinergics, calcium-channel blockers, benzodiazepines, and dopamine [5]. Additional risk factors that have been identified in adults are alcohol consumption, smoking, connective tissue diseases (particularly scleroderma) [6], and chronic obstructive pulmonary disease [7].…”
Section: Incidencementioning
confidence: 99%
“…These agents are useful in patients with moderate symptoms [5].

Cisapride is a serotoninergic agent that increases acetylcholine release in the gastrointestinal tract.

…”
Section: Treatment Of Germentioning
confidence: 99%